2011
DOI: 10.1186/1471-2393-11-95
|View full text |Cite
|
Sign up to set email alerts
|

Risk of placenta previa in second birth after first birth cesarean section: a population-based study and meta-analysis

Abstract: BackgroundObjective: To compare the risk of placenta previa at second birth among women who had a cesarean section (CS) at first birth with women who delivered vaginally.MethodsRetrospective cohort study of 399,674 women who gave birth to a singleton first and second baby between April 2000 and February 2009 in England. Multiple logistic regression was used to adjust the estimates for maternal age, ethnicity, deprivation, placenta previa at first birth, inter-birth interval and pregnancy complications. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
2
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(78 citation statements)
references
References 63 publications
4
66
2
6
Order By: Relevance
“…A study by Gurol-Urganci I et al, shows a rate of 8.7 per 1000 women of placenta previa in women who had 1 prior C-section. 20 Mine study showed 3% placenta previa and 0.5% placenta accrete. Dense adhesion between intra peritoneal organs obstructing operative field were seen in 21 In a study by Vidyadhar et al, admission rate to NICU was 4% where as it 22% in a study by Nilanchali et al, and 27% in Shruti S Goel and et al, study.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Gurol-Urganci I et al, shows a rate of 8.7 per 1000 women of placenta previa in women who had 1 prior C-section. 20 Mine study showed 3% placenta previa and 0.5% placenta accrete. Dense adhesion between intra peritoneal organs obstructing operative field were seen in 21 In a study by Vidyadhar et al, admission rate to NICU was 4% where as it 22% in a study by Nilanchali et al, and 27% in Shruti S Goel and et al, study.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 C-section can also compromise future pregnancies, and have long term negative effects for the newborns, such as obesity, asthma, type-1 diabetes, and lead to unexplained stillbirths in the second pregnancy. 2,[6][7][8][9][10][11][12] These risks explain why c-section on demand is considered, "an expensive and dangerous luxury". 13 Current evidence strongly advises against unnecessary c-sections.…”
Section: Introductionmentioning
confidence: 99%
“…Por ello, la tasa de incidencia de anomalías placentarias se espera que aumente. Según este estudio, en mujeres con cicatriz de cesárea previa, la incidencia de anomalías placentarias fue de 46,2 / 1000 pacientes y sin cicatriz de cesárea previa 5,9 / 1000, siendo valores superiores a los datos que informan otros estudios de placenta previa: 8,7 / 1000 nacimientos en mujeres con antecedente de nacimiento previo por cesárea en comparación a 4,4 / 1000 nacimientos en mujeres con antecedente de parto vaginal anterior (OR ajustada 1,88) (35)(36)(37)(38)(39)(40).…”
Section: Discussionunclassified
“…Los resultados perinatales de pacientes con placenta previa comparados al grupo control referidos en la literatura encontraron 14 veces la probabilidad de parto prematuro que la población sin anomalías placentarias: 41,1% vs. 4,8% p < 0,0001. El análisis estratificado no mostró diferencia significativa en la mediana del peso al nacer, el Apgar en el primer y quinto minuto fue de puntaje mayor que la población con placenta previa: primer minuto (6 vs 10) y al quinto minuto (8 vs.10) (35,36).…”
Section: Discussionunclassified